What factors are associated with advance care planning in community-dwelling older people? Data from TILDA - Kenny, Rose; Briggs, Robert; Lavan, Amanda (My University, 2022)
Purpose: To assess advance care planning (ACP) in a large population-representative sample of older people. Methods: At Wave 4 of the Irish Longitudinal Study on Ageing, participants were asked: Have you made your wishes/preferences known about the kind of care that you would like to receive in the event of serious illness? Results: One quarter (1153/4831) had discussed ACP. Of those, 90% had discussed with family/friends, 10% documented ACP in writing, while 2% had discussed with a healthcare professional. Age ≥ 80 years [OR 1.63 (1.31-2.02)], female sex [OR 1.58 (1.37-1.83)], higher educational attainment [OR 1.42 (1.18-1.71)], poorer self-rated health [OR 1.67 (1.06-2.62)] and lower levels of religiosity [OR 1.50 (1.02-2.19)] were independently associated with ACP. Conclusion: Only one in four older people had discussed ACP informally, while less than 3% have ACP documented in writing. Further work is required to educate the public and healthcare professionals regarding treatment choices at end-of-life.
PUBLISHED
cited By 0
Keywords: Advance care planning, End of life, Older, Palliative care; Ageing